2019
DOI: 10.1016/j.cimid.2019.101372
|View full text |Cite
|
Sign up to set email alerts
|

Wild Bonelli’s eagles (Aquila fasciata) as carrier of antimicrobial resistant Salmonella and Campylobacter in Eastern Spain

Abstract: Wild birds have repeatedly been found to be involved in the dissemination of enteric bacterial pathogens in the environment. The aim of this study was to determine the occurrence of Salmonella and Campylobacter as well as the antimicrobial resistance in wild Bonelli's eagles nestlings in Eastern Spain. In addition, we compared the efficiency of two sampling methods (fresh faecal samples from nest and cloacal swabs from nestlings) for detection of both bacteria. A total of 28 nests with 45 nestlings were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…The confirmed isolates were tested against a panel of 12 antibiotics, and the highest phenotypic resistant displayed by the Campylobacter species was to clindamycin (95.68%) and the lowest was observed against imipenem (21.47%) ( Figure 8 ). Multidrug resistance to azithromycin, ampicillin and ciprofloxacin were observed in the study of Martín-Maldonado et al [ 85 ] and in this study we also observed similar multiple resistance pattern ( Table 3 ). In this study, high phenotypic Campylobacter resistance to ciprofloxacin (77.78%) was observed and this finding corroborate with the report of Meistere et al [ 86 ], who also reported high phenotypic resistance to ciprofloxacin (93.6%) in Campylobacter isolates.…”
Section: Discussionsupporting
confidence: 89%
“…The confirmed isolates were tested against a panel of 12 antibiotics, and the highest phenotypic resistant displayed by the Campylobacter species was to clindamycin (95.68%) and the lowest was observed against imipenem (21.47%) ( Figure 8 ). Multidrug resistance to azithromycin, ampicillin and ciprofloxacin were observed in the study of Martín-Maldonado et al [ 85 ] and in this study we also observed similar multiple resistance pattern ( Table 3 ). In this study, high phenotypic Campylobacter resistance to ciprofloxacin (77.78%) was observed and this finding corroborate with the report of Meistere et al [ 86 ], who also reported high phenotypic resistance to ciprofloxacin (93.6%) in Campylobacter isolates.…”
Section: Discussionsupporting
confidence: 89%
“…Colistin (polymyxin that acts in the destructuring bacterial cell membrane) has been screened by different studies phenotypically on Campylobacter spp. [ 64 , 66 – 68 ]. However, the current study tested this antibiotic genotypically, resulting in 42.1% of the isolates carrying the mcr-4 gene that encodes for colistin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…concheus in Pygoscelis adeliae and Pygoscelis antarcticus [ 28 ]. Campylobacter has also been found in wild birds living in the wild and housed in rescue centres [ 16 , 17 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%